A Conceptual Model of Social Networking in Higher Education - Jucevičienė, P.; Valinevičienė, G. (Elektronika ir Elektrotechnika, 2010)
The popularity of social networking sites has led educators to the idea of engaging learners with their studies. After reviewing the potential areas of social network sites employment in higher education, essential social network software tools were composed in a conceptual model. This model covers most popular areas of social networking possibilities in higher education and is generic enough to make it suitable for any higher education organization.